Comportamento territorial e hierarquia de dominância de Anthracothorax nigricollis Vieillot 1817 (Aves: Trochilidae) em recursos alimentares - Araújo-Silva, Lucas Eduardo (2010)
Dominant species are those which delimit and defend territories from other individuals of the same or different species. Subordinate species are those which, furtive and sneakily, use sources of nectar from other individuals. This study aimed to describe the aggressive interactions between species of hummingbirds, define which species are dominant and which are subordinate, investigate if the sharing of resources occurs during the visits, and compare the behaviour of the dominant species in different strata (tree, arbustive and herbaceous). The species observed interacting with Anthracothorax nigricollis Vieillot 1817 were Phaethornis pretrei Lesson and Delattrer 1839, Thalurania furcata Gmelin 1788, and Polytmus guainumbi Pallas 1764. Nine behavioural acts grouped into four categories were identified and described. The dominant species is A. nigricollis (with 0.9 of the attacks), followed by T. furcata (with 0.07) and P. pretrei (with 0.03). The resource sharing was seen only in the shrub layer, in C. surinamensis, in which there was intraspecific and interspecific sharing. A. nigricollis showed higher interspecific toleration, T. furcata (0.27) and P. pretrei (0.55) than intraspecific A. nigricollis (0.18). The frequency of occurrence of behaviours expressed by A. nigricollis in the three vegetation strata differed significantly.